(untitled) (Indonesian Journal of Science and Technology, 2025)
Rhizophoraceae is a mangrove family that spread from landward to seaward zones and dominated Benoa Bay in Bali, Indonesia. Mangroves are already studied in many approaches but insufficient in anatomical approach. This research aims to determine the anatomical characteristics of Rhizophoraceae mangrove leaves in Benoa Bay, as well as determine the taxonomic significance. The research was conducted at four locations in Benoa Bay with four mangrove species: Bruguiera gymnorhiza, Ceriops tagal, Rhizophora apiculata, and Rhizophora mucronata. Leaf anatomical data was collected by using a modified free-hand section method to obtain leaf transversal structure and replica paradermal to obtain epidermal structure. The data analyzed descriptively and completed with a numerical taxonomy approach by dendrogram and principal component analysis (PCA). Mangrove leaves have general structures such as epidermis, palisade mesophyll, sponge mesophyll, vascular bundles, and stomata, as well as several typical structures such as hypodermis layer, calcium oxalate crystals, and sclereids. The results of the numerical taxonomic analysis revealed several characteristics with taxonomic significance were occurrence of astrosclereid, number of upper hypodermal layers, thickness ratio of hypodermal to lamina, thickness ratio of mesophyll palisade to sponges, thickness ratio of mesophyll sponges to lamina, and type of stomata.